Circulating Long Non-Coding RNA GAS5: A Non-Invasive Molecular Marker for Prognosis, Response to Treatment and Survival in Non-Small Cell Lung Cancer. (9th August 2021) - Al Mourgi, Majed; El Askary, Ahmad; Gharib, Amal F.; Alzahrani, Rajab; Banjer, Hamsa Jameel; Elsawy, Wael H.; Al Ghamdi, Abd El-Rahman; Raafat, Nermin
Abstract: Circulating long non-coding RNAs (lncRNA) are dysregulated in several diseases, especially cancers, e.g. non-small-cell lung cancer (NSCLC). Of specific notice in this regard is growth arrest-specific 5 gene (lncRNA GAS5), which is principally recognised as a tumor suppressor gene in numerous cancers. Functionally, GAS5 is involved in arresting cellular growth and induction of apoptosis. We analysed plasma GAS5 expression by qRT-PCR in 100 patients with NSCLC before and after tumour resection surgery. We reported a downregulation of GAS5 expression in NSCLC tissue and plasma, which showed elevation after surgery. Downregulation of GAS5 was associated with poor prognosis of NSCLC patients.